Dependence of PINK1 accumulation on mitochondrial redox system. Issue 9 (11th August 2020) - Gao, Feng; Zhang, Yan; Hou, Xiaoou; Tao, Zhouteng; Ren, Haigang; Wang, Guanghui
Abstract: Accumulation of PINK1 on the outer mitochondrial membrane (OMM) is necessary for PINK‐mediated mitophagy. The proton ionophores, like carbonyl cyanide m‐chlorophenylhydrazone (CCCP) and carbonyl cyanide‐4‐(trifluoromethoxy)phenylhydrazone (FCCP), inhibit PINK1 import into mitochondrial matrix and induce PINK1 OMM accumulation. Here, we show that the CHCHD4/GFER disulfide relay system in the mitochondrial intermembrane space (IMS) is required for PINK1 stabilization when mitochondrial membrane potential is lost. Activation of CHCHD4/GFER system by mitochondrial oxidative stress or inhibition of CHCHD4/GFER system with antioxidants can promote or suppress PINK1 accumulation, respectively. Thus data suggest a pivotal role of CHCHD4/GFER system in PINK1 accumulation. The amyotrophic lateral sclerosis‐related superoxide dismutase 1 mutants dysregulated redox state and CHCHD4/GFER system in the IMS, leading to inhibitions of PINK1 accumulation and mitophagy. Thus, the redox system in the IMS is involved in PINK1 accumulation and damaged mitochondrial clearance, which may play roles in mitochondrial dysfunction‐related neurodegenerative diseases. Abstract : PINK1 is accumulated on the depolarized mitochondria dependent on the disulfide relay system in the IMS. Unfolded PINK1 enters the IMS through the TOM and interacts with oxidized CHCHD4 to avoid releasing to cytosol from the membrane potential lost mitochondria. The PINK1 in the TOM complex is further transported into the OMM through some proteins in the TOM.